QUALITY OF LIFE AFTER LAPAROSCOPIC SLEEVE GASTRECTOMY USING BAROS SYSTEM - Kirkil, Cuneyt; Aygen, Erhan; Korkmaz, Mehmet Fatih; Bozan, Mehmet Bugra (Colegio Brasileiro Cirurgia Digestiva-Cbcd, 2018)
Background: Laparoscopic sleeve gastrectomy (LSG) is currently the most frequently performed bariatric procedure in Turkey. The goal of weight reduction surgery is not only to decrease excess weight, but also to improve obesity related comorbidities and quality of life (QoL). Aim: To evaluate the impact of LSG on patient quality of life, weight loss, and comorbidities associated with morbid obesity according to the updated BAROS criteria. Methods: Eleven hundred thirty-eight adult patients were undergone to LSG by our bariatric surgery team between January 2013 and January 2016. A questionnaire (The Bariatric Analysis and Reporting Outcome System - BAROS) was published on social media. The data on postoperative complications were collected from hospital database. Results: Number of respondants was 562 (49.4%). Six of 1138 patients(0.5%) had leakage. All patients who had leakage were respondants. The overall complication rate was 7.7%. After a mean period of 7.4 +/- 5.3 months(1-30), mean excess weight loss was 71.3 +/- 27.1% (10.2-155.4). The respondants reported 772 comorbidities. Of these, 162 (30%) were improved, and 420 (54.4%) were resolved. The mean scores for QoL were significantly increased after LSG (range, p<0.05 to <0.001). Of the 562 patients, 26 (4.6%) were classified as failures; 86 (15.3%) fair; 196 (34.9%) good; 144 (25.6%) very good, and 110 (19.6%) excellent results according to the updated BAROS scoring system. Conclusion: LSG is a highly effective bariatric procedure in the manner of weight control, improvement in comorbidities and increasing of QoL in short-and mid-term.
Qualidade de vida após gastrectomia vertical laparoscópica usando o sistema BAROS
Keywords: Obesity; Sleeve gastrectomy; Quality of life; Bariatric surgery